Hubungan Pengetahuan Dengan Peran Diri Pasien Diabetes Mellitus Di RS Mardirahayu Kudus - Devi Setya Putri (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstract The number of Diabetes Mellitus (DM) sufferers is increasing. The high prevalence of diabetes mellitus sufferers is caused by several risk factors, one of which is self-knowledge and role. Role self refers to healthy eating, physical activity, blood sugar monitoring, medication adherence, positive problem solving, coping skills and risk reduction behaviors. The role of self is determined from the patient's knowledge. This study aims to determine the relationship between knowledge and the role of diabetes mellitus patients at Mardi Rahayu Kudus Hospital. Analytical correlational research type with cross sectional design. The population is diabetes mellitus sufferers at Mardi Rahayu Kudus Hospital. The sampling technique is purposive sampling. The sample size was 65 people. Statistical data analysis using the Spearman Rank test. The result got knowledge was in the medium category 32 (49.2%), role self was the most in the role satisfaction category 44 (67.7%). Spearman Rank analysis obtained a p value of 0.000 and a rho value of (0.605). There is a strong relationship between knowledge and the role of diabetes mellitus patients at Mardi Rahayu Kudus Hospital because the p value (0.000) is <0.05 at the 5% significance level. Keywords: Knowledge, Self Role, Diabetes Mellitus.